MENGHITUNG HPP MENGGUNAKAN METODE ABC PADA USAHA IKAN KERING BAPAK SYAHRUL DI DESA LANGKAK - Ulfa, Fitria; Nugroho, Yoga (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The current global era is the competitiveness of various business actors in facing market competition, where every producer, especially SMEs must not only create quality and innovative products, but also be able to compete in the market with other business actors. Accurate calculation of cost of production is necessary in order to produce clear sales information for each product sold. The purpose of this study was to determine the cost of production in the dried fish business owned by Mr. Syahrul according to the activity-based costing system (ABC system). This type of research is applied research. Data collection methods include documentation and interviews. Data analysis includes identifying activities, assigning costs to activities, grouping activities, calculating group rates, and manufacturing overhead costs (BOP). The results of this study indicate that the cost of production using the traditional accounting system is higher than the Activity Based Costing system, so that the profit with the Activity Based Costing system is higher than the traditional accounting system. Structurally based on cost drivers and data sources consumed by products in the dried fish business. Mr. Syahrul, which will have an impact on the collection of actual dried fish production costs.